2020
DOI: 10.32598/irj.18.1.655.1
|View full text |Cite
|
Sign up to set email alerts
|

Marital Satisfaction and Happiness in Parents With Autistic and Normal Children

Abstract: The present study was conducted to compare the relationship between marital satisfaction and happiness in parents of autistic and normal children. Methods: This causal-comparative research was conducted on all parents of autistic and normal children who referred to the rehabilitation clinics in Tehran in 2017. Using available sampling, 220 parents (110 parents with autistic and 110 parents with normal children) were selected. Data collection was done using the Enrich Marital Satisfaction Scale and Oxford Happi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Absence of communication with the spouse due to the increased caregiving demands along with the lack of acceptance of child's autism makes the marital relationship vulnerable. This is in congruence with the findings of Gau et al (2012) which reports that mothers of children with autism perceived less marital satisfaction and that of Hoseinnejad et al (2020) which points to a possible relationship between the autism disorders of children and their parents' marital satisfaction and happiness. The conspicuous changes in the marital relationship have an influence on their family planning.…”
Section: Discussionsupporting
confidence: 90%
“…Absence of communication with the spouse due to the increased caregiving demands along with the lack of acceptance of child's autism makes the marital relationship vulnerable. This is in congruence with the findings of Gau et al (2012) which reports that mothers of children with autism perceived less marital satisfaction and that of Hoseinnejad et al (2020) which points to a possible relationship between the autism disorders of children and their parents' marital satisfaction and happiness. The conspicuous changes in the marital relationship have an influence on their family planning.…”
Section: Discussionsupporting
confidence: 90%
“…The differences are statistically significant. It turns out that there is a connection between ASD in children and the happiness, as well as marital satisfaction, of the parents (Hoseinnejad et al, 2020). Meanwhile, a strong marital relationship is regarded as essential, because it provides care and emotional or physical support (Koydemir-Özden and Tosun, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] In addition to the financial burden of care, studies in various parts of the world have shown that having a child with ASD is often associated with poor quality of life in social, psychological, and physical dimensions as well as reduced happiness. [ 14 15 ] The results of previous studies show that parents of children with ASD consistently experience higher levels of stress than parents of normal children and even parents of children with other psychiatric and developmental disorders (for example, Down syndrome, fragile X syndrome, and cerebral palsy). [ 16 ] Sleep disorders, physical problems, lack of social interaction, marital conflict, financial problems, insufficient time to spend on health issues, and chronic stress are the challenges that parents of autistic children face.…”
Section: Introductionmentioning
confidence: 99%